RESEARCH ON THE POLICY OPERATION EVALUATION AND OPTIMIZATION PATH OF THE ENTREPRENEURSHIP AND EMPLOYMENT OF COLLEGE GRADUATES IN XINXIANG - Ma, Zhijun (International Journal of Research -GRANTHAALAYAH, 2023)
Employment is the foundation of people’s livelihood, and entrepreneurship is the foundation of employment. This article analyzes the implementation effect and existing problems of the policies that have been introduced by Xinxiang City to promote the entrepreneurship and employment of graduates in Xinxiang City, and puts forward the methods of optimizing policies such as taking into account all levels and elements of the policy, improving the publicity system of entrepreneurship and employment policies, formulating diversified entrepreneurship and employment subsidy policies, and increasing the support of college students’ entrepreneurship policies.